Illuminating Women's Hidden Contribution to Historical Theoretical Population Genetics. - Dung, Samantha Kristin; López, Andrea; Barragan, Ezequiel Lopez; Reyes, Rochelle-Jan; Thu, Ricky; Castellanos, Edgar; Catalan, Francisca; Huerta-Sánchez, Emilia; Rohlfs, Rori V. (Genetics, 2019)
While productivity in academia is measured through authorship, not all scientific contributors have been recognized as authors. We consider nonauthor "acknowledged programmers" (APs), who developed, ran, and sometimes analyzed the results of computer programs. We identified APs in Theoretical Population Biology articles published between 1970 and 1990, finding that APs were disproportionately women (P = 4.0 3 10-10). We note recurrent APs who contributed to several highly-cited manuscripts. The occurrence of APs decreased over time, corresponding to the masculinization of computer programming and the shift of programming responsibilities to individuals credited as authors. We conclude that, while previously overlooked, historically, women have made substantial contributions to computational biology.